Meningkatkan Kemampuan Berhitung Anak Melalui Permainan Ular Tangga (PTK Di Tk Satu Atap SD Negeri 3 Talang Padang) - Putri, Novita (CV. Generasi Insan Rafflesia, 2024)
This class action research aims to improve the counting ability of children aged 4 - 5 years with snakes and ladders game in group A of Tk Satu Atap SD 3 Talang Padang. The method used in this research is collaborative classroom action research using the Kemmis and Mc Taggart model. PTK is carried out as an effort to overcome problems that arise in the classroom. This method is carried out with four stages, namely planning, action, implementation, and reflection. The research subjects were group A students of Tk Satu Atap SD 3 Talang Padang, totalling 10 children. The object of this research is the counting ability of children aged 4 - 5 years. The data collection method used was observation. Technical data analysis was carried out descriptively qualitative and quantitative. The success indicator set is at least 75% of 10 children achieving counting ability of children aged 4 - 5 years. This research was conducted in two cycles.The results showed that the counting ability of children aged 4 - 5 years has increased. The increase in counting ability of children aged 4 - 5 years can be seen from the indicators of the ability to count objects 1 - 10, recognise number concepts, recognise number symbols 1 - 10, mention number symbols 1 - 10, match numbers with number symbols. The increase in counting ability of children aged 4 - 5 years with snakes and ladders games in the implementation of pre-action 31, 5%, and in cycle I increased to 51.5%, because it is still less than the success criteria that should be, the next action is cycle II and increases very well by getting a percentage of 85%. With this acquisition, the research was stopped because it had reached the success criteria.